IMPROVING LISTENING SKILLS: STRATEGIES AND TECHNIQUES - Eshonqulov Ravshan Toxirovich; Jurayev Azizbek Ikromjon ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Listening is a crucial skill for effective communication, yet it is often underdeveloped compared to other forms of interaction. This article explores strategies and techniques to improve listening skills, emphasizing the importance of active listening and concentration. Drawing on insights from renowned authors like Stephen Covey, Erich Fromm, and Stephen Krashen, the article discusses various aspects of listening, including the distinction between hearing and listening, the role of mindfulness and focus, and the impact of vocabulary and background knowledge on comprehension. Additionally, the article outlines different types of listening—informational, critical, and empathetic—and provides practical exercises such as paraphrasing, note-taking, and mind mapping to enhance listening abilities. Special attention is given to the challenges of listening in a second language and the value of self-reflection in refining listening habits. Ultimately, the article presents listening as a dynamic, skill-building process that can be developed through consistent practice and awareness, offering readers practical tools to become more effective communicators.